Possible society in Latin American political speech: Miranda, Bolívar, Sarmiento, and Martí - Morales, Gerardo (2018)
In this article we analyze Latin America as a region where the concept of “possible society” has been considered many years ago. This kind of society in Latin America is a social and civic project in which solidarity, justice, and equality can be totally developed as a nation project.